The Cyborg Search Fatal Error: The Images of MU Online - Garcia, Kim Homer C. (Review of Women's Studies; Vol 20 No 1-2 (2010): Review of Women's Studies Volume XX, Numbers 1-2 (January-December 2010))
This essay aims to investigate the possibility of a post-gender world, as posited by D. Haraway, and of the possibility of freedom for women within cyberspace, as proposed by S. Plant, by analyzing the dynamics of online gaming. It asserts that the cyberspace is a male-created and dominated world that does not allow for the emergence of the cyborg.